Chemical and hedonic characteristics of smoked Katsuwonus pelamis (fufu fish) from Sorong, West Papua, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sayuti M, Salampessy RBS, Asriani, Nurbani SZ, Saidin. 2022. Chemical and hedonic characteristics of smoked Katsuwonus pelamis (fufu fish) from Sorong, West Papua, Indonesia. Biodiversitas 23: 1707-1713. Fufu fish is one of the smoked fish products from eastern Indonesia, especially the North Sulawesi and Papua region, with raw materials derived from skipjack tuna or yellow-fin tuna. Samples were obtained from fish-smoking entrepreneurs in Sorong City. Proximate analysis was carried out using the association of official analytical chemist (AOAC) standard, amino acid analysis was carried out using liquid chromatography-mass spectrometry (LC-MS), fatty acid analysis was carried out using gas chromatography-mass spectrometry (GC-MS), and hedonic analysis was carried out using the SNI 2346:2015 standard with 120 panelists. The results showed that fufu fish had a water content of 64.52%, ash content of 0.82%, total fat of 1.97%, protein of 27.75%, carbohydrates of 4.37%, and crude fiber of 2.69%. The main essential amino acids of fufu fish were L-Lycine by 5.59%, L-Histidine by 3.25%, and L-Leucine by 2.61%. On the other hand, the main non-essential amino acids were L-Glutamic acid by 3.83%, L-Aspartic acid by 2.60%, and L-Arginine by 2.43%. The main fatty acids of fufu fish were C15:1 (cis-10) by 47.43%, C14:0 by 16.75%, C16:0 by 12.20%, and C18:0 by 10.97%. On the fufu fish hedonic test results, the panelists generally gave a like score. Based on these findings, it can be concluded that fufu fish had good nutritional content for the community.
Keywords: Amino acid, fatty acid, hedonic test, proximate, smoked fish